THEORETICAL EXPLORATION OF ART THERAPY AND EDUCATION FOR AUTISTIC CHILDREN - Muchammad Bayu Tejo Sampurno; Yayi Suryo Prabandari; Martinus Dwi Marianto (IJIET (International Journal of Indonesian Education and Teaching), 2020)
This paper aims to explore art therapy methods that are able to become one of the complementary media to improve the communication skills of children with autism; explain concretely the contribution of art flexibility as a complementary media in communication therapy for autistic children; and explain the integration of the principles of therapy. These three topics will be explored using a number of theories about art therapy that have developed, as a research beginning on the development of methods of art therapy and art education for autistic children. The approach in this study uses the method of content analysis of the phenomenon of art therapy, which is implemented as a perspective to see the phenomenon of art education for autism in Yogyakarta, Indonesia in 2019. This study begins with a study of the development and patterns of art therapy which has been going on in Indonesia. Afterwards, the current foothold of art therapy will be known, and able to explain the reasons related to the development of art therapy in Indonesia. The results showed that the models of art therapy and art education for autistic children in Indonesia did not include the development of art therapy, learning methods through play, and did not understand the empathy space as a learning space for autistic children. Art exploration has good potential to be developed as a method of therapy and education for autistic children. That is because, art has the flexibility and natural nature of children, namely playing and making a sense of comfort, so that autistic children feel in one frequency with the teacher so that the educational and therapeutic process runs smoothly and optimally. The emergence of the concept of 3B (being, becoming, and belonging) in the space of empathy, increasingly claims that art cannot be separated in the world of learning in autistic children.